Analisis Tingkat Kapitalisasi Sewa Properti Rumah Toko dan Faktor-Faktor yang Mempengaruhinya di Kota Medan - Bambang Hadi Syahputra; Khaira Amalia; Parapat Gultom (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
The development of the property sector in Indonesia over the past few decades has shown significant dynamics in line with national economic growth and the increasing need for residential, commercial, and industrial space. One property segment that has experienced rapid growth is shophouses (ruko), especially in urban areas that are centers of economic growth and trade, such as Medan. The rate of return on commercial property investment in Medan shows significant variation, but there is still little research specifically analyzing the physical and spatial factors that influence the rental capitalization rate of shophouses (ruko). This study aims to analyze the rental capitalization rate of shophouses in Medan and identify the factors that influence it. The study used a quantitative approach with a multiple linear regression method. Data were obtained from property listings, field observations, and secondary sources from the Central Statistics Agency. A sample of 180 shophouses spread across several areas of the city was selected. The results showed that building area (p 0.001), land area (p 0.000), and number of floors (p 0.021) had a positive and significant effect on the rental capitalization rate of shophouses. The variables of area type, road type, and population density did not significantly influence the rental capitalization rate of shophouses. The physical characteristics of a shophouse play a more dominant role in determining its investment attractiveness than its location. Investors and shophouse owners need to emphasize evaluating space utilization efficiency, tenant stability, and rental income potential when determining investment feasibility and rental pricing strategies. A contextual, local market-based property valuation approach is crucial in commercial property capitalization studies.